Endosulfan Elimination Using Amine-Modified Magnetic Diatomite as an Adsorbent - Alacabey, İhsan (Frontiers in Chemistry, 2022)
Pesticides are one of the most dangerous developing toxins since they are very hazardous to the environment and constitute a risk to human health. In this study, researchers successfully manufactured surface-modified magnetic diatomite (m-DE-APTES) and used them as a sorbent to extract endosulfan from an aqueous solution. There is no other study like it in the scholarly literature, and the results are astounding. Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), energy dispersive X-ray (EDX), electron spin resonance (ESR), and surface area measurements were used to analyze magnetic diatomite particles with surface modification. Magnetic diatomite has a wide surface area and a porous structure, according to the analysis results. Furthermore, m-DE-APTES has a higher endosulfan adsorption capacity (97.2 mg g-1) than raw diatomite (DE) (16.6 mg g-1). Adsorption statistics agree with Langmuir adsorption isotherm (R2=0.9905), and the adsorption occurred spontaneously at -2.576 kj mol-1 in terms of ΔGo. Finally, m-DE-APTES are a viable alternative adsorbent for removing pesticides from aqueous solutions.